Transforming growth factors produced by certain human tumor cells: polypeptides that interact with epidermal growth factor receptors. - Todaro, G J (1980)
Three different human tumor lines in culture, a rhabdomyosarcoma, a bronchogenic carcinoma and a metastatic melanoma, release proteins (transforming growth factors, TGFs) into the medium that confer the transformed phenotype on untransformed fibroblasts. These proteins are acid and heat-stable; produce profound morphologic changes in rat and human fibroblasts; and enable normal anchorage-dependent cells to grow in agar. Removal of the transforming protein results in a reversion of cell phenotype. The major activity interacts with epidermal growth factor (EGF) cell membrane receptors. The peptides from these tumor cells are similar in their action to the sarcoma growth factor (SGF) released by murine sarcoma virus-transformed rodent cells. The most anchorage-independent tumor cells released the most TGFs. EGF-related TGFs were not detectable in fluids from cultures of cells with high numbers of free EGF membrane receptors (normal human fibroblasts and human carcinomas).